Identificação e verificação de atividade celulolítica de microrganismos isolados de compostagem - Paganini, Thais Pires Martins [UNIFESP] (2016)
The composting process is an effective and economical way of treating organic waste, mainly by microbial decomposition. The Fundação Parque Zoológico de São Paulo (FPZSP) has a compost production unit (UPCO) that takes organic matter from various sources, and one of the waste more used in the process are vegetable scraps, and consequently cellulose is the largest source of carbon present. This study explored the diversity in order to obtain cellulose-degrading microorganisms. Thus, a total of 54 microorganisms were isolated in medium supplemented with carboxymethyl cellulose as sole carbon source. Among them, a specie never described before as cellulose degrading, identified as Gordonia paraffinivorans, showed a high specific activity in enzymatic assays. Further, this microorganism had their genomes sequenced and the analysis of the genome identified sequences encoding two families (GH1 and GH3) of β-glucosidases.